CAUSES OF FATIGUE IN THE BODY DURING PHYSICAL EXERCISE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
The article discusses the causes of fatigue of athletes during sports loads. Health is an invaluable gift that nature presents to a person. In order to preserve sports health and strengthen it, in order to improve health and prevent diseases, it is necessary to engage in physical culture intelligently. To resist adversity, you need to know your body and ensure its ability to overcome harmful influences and consequences by self-healing methods. Each of us needs to strengthen our health gradually. The article discusses the causes of fatigue of athletes during sports loads.